A Review of Nutritional Guidelines and Menu Compositions for School Feeding Programs in 12 Countries - Aliyar, Ruzky; Gelli, Aulo; Hamdani, Salha Hadjivayanis (Frontiers in Public Health, 2015)
Study objectives: To analyze the nutritional guidelines and menu compositions of school meal provision in various different countries. Background: School feeding is the provision of food on-site or to take home, which aims to increase school enrolment, attendance and retention, and exist as a social safety net for households with very low income. Home-grown school feeding (HGSF), additionally, aims to stimulate local economies by providing a source of income for local smallholder farmers. Methods: Literature searches using the Ovid MEDLINE databases, gathered information from in-country stakeholders, and accessed the programme websites of various countries. Nutrient composition of these menus was calculated from nutritional guidelines and menu compositions using a nutrition linear programming tool (NUTVAL). Country comparisons: School feeding aims differ between countries of each income group. The implementation, delivery of service and nutritional content of foods also differ considerably between countries and income groups. In high-income countries, guidelines and standards have been recommended in an attempt to combat rising levels of overweight and obesity, and to model healthier lifestyle habits. In low-income countries there is a gap in terms of guidance on nutrition standards and menu composition. Conclusions: Provision of evidence-based guidance on nutrition standards to middle and low income countries who have recently established or are planning to establish school feeding has the potential to greatly enhance and improve the quality of service and improve the life of millions of children worldwide.